Timber battle in Solomon Islands - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The first shipment of eco-timber from sustainably managed forest in the Marovo Lagoon area in the Solomon Islands reached Australia at the end of 2000, opening up a new eco-export-channel and marking another phase in the battle to maintain...